(untitled) (Journal of Plant Disease Sciences, 2026)
Rice holds significant importance as a staple food grain, contributing about 21% of the total energy intake and nearly 15% of the total protein consumption of humans. Therefore, emphasis on both the quantity and quality of rice production is essential. Diseases in rice cultivation cause substantial annual reductions in both yield and quality. Considering this, the present investigation was undertaken to assess disease incidence and severity and to screen rice varieties against sheath blight in different districts of Madhya Pradesh. A survey conducted across several districts revealed that the maximum disease incidence was recorded in the Kranti variety in Jabalpur district, while the minimum incidence was observed in the Danteshwari variety in Sagar district. The highest disease severity was recorded in the IR-36 variety of Jabalpur district (85.9%), followed by the Kranti variety (72.7%), whereas no disease incidence was observed in Panna district. Atotal of 96 rice varieties were screened against . None of the varieties was Rhizoctonia solani found to be immune; however, one variety was highly resistant, five were resistant, eighty-six were moderately resistant, three were susceptible and one was highly susceptible.